Περί εὐαγοῦς και βασιλικοῦ σεκρέτου στη Θεσσαλονίκη - ΓΚΟΥΤΖΙΟΥΚΩΣΤΑΣ Ανδρέας Ε. (Byzantina Symmeikta, 2022)
The present study examines the evidence for the basilikon sekreton (tribunal) in Thessaloniki. It is concluded that, contrary to what has been assumed, there was no basilikon sekreton in the city during the first half of the 14th century, but only the euages sekreton of Yolanda-Irene Montferrat (1304), the second wife of Andronikos II Palaiologos. The basilikon sekreton in Thessaloniki appeared only after the establishment of the katholikoi kritai of Thessaloniki, as in the case of the katholikoi kritai of Rhomaioi whose tribunal was also named basilikon sekreton. The first references to the basilikon sekreton in Thessaloniki are found in documents dating to 1374 and 1375.